ADAPTING ENGLISH LANGUAGE EDUCATION IN UZBEKISTAN TO INTERNATIONAL STANDARDS - Ergashxo`jayeva M.E.; Gaybullayeva X.M. (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Globalization and international communication have made English an essential language for students worldwide. In Uzbekistan, aligning English language teaching and assessment with international standards, such as CEFR (Common European Framework of Reference), ensures a systematic learning process, accurate skill assessment, and effective learning outcomes. This paper discusses the current situation of English language education in Uzbekistan, examines challenges in applying international standards, and proposes solutions to improve teaching methods and assessment systems.